BRANDING ARAK BALI SEBAGAI ALAT KOMUNIKASI POLITIK GUBERNUR BALI DI KALANGAN MASYARAKAT BALI - Wikadana, Putu Edovan; Erawan, I Ketut Putra; Pramana, Gede Indra; Duarte, Efatha Filomeno Borromeu (Retorika: Jurnal Komunikasi, Sosial dan Ilmu Politik, 2024)
This research aims to describe how Balinese Arak Branding is used as a political communication tool by the Governor of Bali among the Balinese people. This research is a qualitative study with primary data obtained from interviews and secondary data consisting of published documents, scientific articles, as well as print and electronic media. This research used a purposive sampling technique to determine informants, and the data was analyzed using qualitative descriptive methods.The research results show that the Governor of Bali uses Bali Arak as the main symbol in his branding strategy, making it an effective political communication tool. Although the use of arak as a political communication tool is considered controversial, especially considering the ban on the sale of alcoholic arak in Bali in 2015, the Governor of Bali has succeeded in promoting Bali Arak as a strong cultural symbol. With pride, the Governor expressed Balinese cultural identity through Arak Bali, which reflects respect for local heritage and strengthens the community's sense of pride in their culture. This strategy also helps the Governor portray himself as a leader who is committed to maintaining and preserving Balinese traditions, thereby increasing political support among the local community.